Evaluation of dialectal speech in PAPRŪSĖ region: investigation of Vištytis habitat in the beginning of the twenty-first century - Bakšienė, Rima (Lietuvių kalba, 2019)
Vištytis habitat belongs to the western part of Western Highlanders of Kaunas. The border of East Prussia has been in this area, so these environs until are often called as paprūsė region. There is described location of Vištytis habitat in the Lithuanian dialect classification, specific features and dialectal attitudes of speakers in the beginning of the twenty-first century. The results of this research are discussed in comparing to other similar studies of Western Highlanders of Kaunas. The investigation revealed that the speakers of Vištytis sub-dialect tend to consider local speech variant as standard Lithuanian language. The local speech was evaluated by the speakers as partially non-correct, but attractive. This attitude was mostly determined by aspects of intelligibility and conventionality of the local speech code. Evaluation of dialectal speech in Vištytis habitat for the most part coincides with common self–evaluation pattern of Western Highlanders of Kaunas. The short linguistic distance to standard language, fairly high prestige of dialectal speech and the same language code in all linguistic situations are most representative characteristics of this pattern.